Description of Hyloconis longivalvata Li, sp. n., with notes on its biology (Lepidoptera: Gracillariidae, Lithocolletinae) - Cai, Yanpeng; Liu, Tengteng; Li, Houhun (Entomologica Fennica, 2015)
Hyloconis longivalvata Li, sp. n. is described based on adults, larvae and pupae from Tianjin and Shanxi, northern China. Campylotropis macrocarpa (Bunge) and Lespedeza bicolor Turcz. (Fabaceae) are reported as its host plants. The larval head and pupal features of the genus Hyloconis are described for the first time. Morphological characters of adult and immature stages as well as leafmines of the new species are illustrated.